ANALISIS METODE PEMBELAJARAN EFEKTIF TERHADAP MINAT BELAJAR SISWA KELAS V DI SEKOLAH DASAR NEGERI 3 SUDIMARA TANGERANG: ANALISIS METODE PEMBELAJARAN EFEKTIF TERHADAP MINAT BELAJAR SISWA KELAS V DI SEKOLAH DASAR NEGERI 3 SUDIMARA TANGERANG - Zahra Imelda -; Maisya Tamami Nufus; Mosa Lantiani; Rahmawati Eka Saputri (STKIP Subang, 2025)
This research was conducted to find out the analysis and relationship between effective learning methods and learning interest of grade V students at Sudimara 3 State Elementary School, this research uses descriptive qualitative methods which include observation and interviews. The results showed that 95% of 28 students liked fun learning methods such as group discussion-based learning methods, educational games, quizzes, learning videos and project-based learning approaches. Then there are 71% of 28 students who can answer the quiz well and correctly. Students with high learning interest were more active and enthusiastic, while students with low learning interest were passive. It can be concluded that effective learning methods have an influence on student interest in learning. With the analysis of effective learning methods, it can increase students' interest in learning by determining the most suitable and interesting approach for them in the learning process.